Cancer Evo–Dev: A Theory of Inflammation-Induced Oncogenesis - Liu, Wenbin; Deng, Yang; Li, Zishuai; Chen, Yifan; Zhu, Xiaoqiong; Tan, Xiaojie; Cao, Guangwen (Frontiers in Immunology, 2021)
Chronic inflammation is a prerequisite for the development of cancers. Here, we present the framework of a novel theory termed as Cancer Evolution-Development (Cancer Evo-Dev) based on the current understanding of inflammation-related carcinogenesis, especially hepatocarcinogenesis induced by chronic infection with hepatitis B virus. The interaction between genetic predispositions and environmental exposures, such as viral infection, maintains chronic non-resolving inflammation. Under the microenvironment of non-resolving inflammation, pro-inflammatory factors facilitate the generation of somatic mutations and viral mutations by inducing the imbalance between the mutagenic forces such as cytidine deaminases and mutation-correcting forces including uracil–DNA glycosylase. Most cells with somatic mutations and mutated viruses are eliminated in survival competition. Only a small percentage of mutated cells survive, adapt to the hostile environment, retro-differentiate, and function as cancer-initiating cells via altering signaling pathways. These cancer-initiating cells acquire stem-ness, reprogram metabolic patterns, and affect the microenvironment. The carcinogenic process follows the law of “mutation-selection-adaptation”. Cancer Evo-Dev not only help understand the mechanisms by which inflammation promotes the development of cancers, but also lays the foundation for specific prophylaxis and targeted therapy of various cancers.